Encysted hydrocele of the canal of Nuck in an 11-month-old child with a past history of duodenal atresia and Arnold-Chiari malformation: A case report. Issue 4 (January 2019) - Zvizdic, Zlatan; Milisic, Emir; Chikha, Adisa; Sefic, Irmina; Dzananovic, Amra; Vranic, Semir
Abstract: Rationale: Hydrocele of the canal of Nuck is a rare developmental disorder and represents of a homolog of hydrocele of spermatic cord in males. Hydrocele of the canal of Nuck is a very rare cause of inguinal swelling in female infants and children. It results from the failure of obliteration of the distal portion of evaginated parietal peritoneum within the inguinal canal, which forms a sac containing fluid. Patient concerns: We describe a case of hydrocele of the canal of Nuck in an 11-month-old girl with a past medical history of duodenal atresia and Arnold-Chiari malformation. Diagnosis: Physical examination and ultrasound revealed a soft, cystic, noncompressible, and non-fluctuant labial mass measuring approximately 5 cm. Interventions: The patient underwent surgical exploration through a right skin crease incision. The cystic lesion was histologically confirmed to be a non-communicated hydrocele of canal of Nuck. Outcomes: The child is doing well at 1-year follow-up with no swelling or recurrence on the operated side. Lessons: Hydrocele of the canal of Nuck is a rare developmental disorder but should be considered in a differential diagnosis in young girls with an inguino-labial swelling.